Insecticidas orgánicos en el control de la cochinilla harinosa Dysmicoccus brevipes Cockerell 1893, en el cultivo de piña (Ananas comosus L.). - Morales Mora, Dayana Jennyfer (2024)
Pineapple cultivation has experienced notable growth worldwide, countries such as Costa Rica, the Philippines and Thailand have become the main producers and exporters. In Ecuador, pineapple cultivation has acquired great economic and agricultural importance, with around 7,000 hectares of plantations and a significant increase in exports. The presence of the mealybug D. brevipes represents a challenge for pineapple cultivation, and the use of organic insecticides is presented as a sustainable alternative for its control. The purpose of this research was to determine the effectiveness of organic insecticides in the control of D. brevipes in pineapple crops (Ananas comosus L.), the methodology used was through analysis of magazines, current texts, articles, synthesis and summary of the data collected. The results showed that organic insecticides use several mechanisms to combat the pest, including direct contact through ingestion or contact with the insecticide. Botanicals, such as neem, garlic and chili extract, have been shown to be highly effective in controlling D. brevipes. In conclusion, the importance of organic insecticides lies in their ability to provide a friendly solution to the environment and human health by minimizing their negative impact. Its proper application not only protects pineapple crops from damage caused by the pest, but also contributes to maintaining the quality and safety of the harvested products.